Identification and characterization of apoptosis-associated speck-like protein gene of Micropterus salmoides - Chao Yang; Junjian Dong; Chengfei Sun; Yuanyuan Tian; Zhigang Liu; Fengying Gao; Hetong Zhang; Xing Ye (Aquaculture Reports, 2022)
Apoptosis-related speck-like protein (ASC) is a key adapter protein in many inflammasome protein complexes, which mediates inflammation and host defense. In this study, an ASC gene (named Msasc) was identified and cloned from the liver tissue of Micropterus salmoides. The full-length cDNA sequence of Msasc was 573 bp, encoding 190 amino acids. Protein prediction shows that MsAsc contains two conserved domains, including the pyrin domain and caspase recruitment domain. The tissue distribution of Msasc mRNA in M. salmoides was investigated using the qPCR method. The expression of this gene could be detected in eight types of tissues, among which the heart, gill, and liver tissues showed a relatively higher expression level; the expression level was the lowest in the brain. When infected with Aeromonas veronii, the expression of Msasc in the spleen and liver tissues of M. salmoides reached its peak at 24 h after infection. Cell transfection experiment showed that MsAsc was distributed in HeLa cells in a diffuse manner. Results of the immune challenge experiment revealed that the inflammasome stimulator nigericin could markedly induce the aggregation of MsAsc in HeLa cells. These results suggest that Msasc is involved in the immune response of M. salmoides to A. veronii infection. This study lays a foundation for an in-depth understanding of the antibacterial function of Msasc in M. salmoides.